Infection of Cord Blood and Embryos at Early Gestation Terms and Hemopoiesis in Embryonic Liver - Lobyntseva, G. S.; Vorozhka, I. V.; Sitnikova, A. V. (Problems of Cryobiology and Cryomedicine, 2008)
With PCR there were studied the samples of placenta, maternal and cord blood. The total number of infected samples for cord blood made 5.4% and 20% for placenta. There were no data on the presence of infectious diseases in anamnesis of parturient women. The investigation of abortive embryos has shown that 47% were differently infected, and they can be found even at 6–10 developmental weeks. There was studied the cell composition of hemopoietic cell population isolated form embryonic liver of 7–12 gestation weeks’ fetuses and its change was established when revealing the intrauterine infections.